A Dual‐Channel Charge Transfer Heterostructure toward Boosting Photocatalytic Hydrogen Evolution. Issue 14 (23rd March 2022) - Yang, Yurong; Wang, Jiahui; Ma, Yuanchi; Qiu, Min; Yan, Guomin; Chen, Jiaming; Gao, Fan
Abstract: The design and fabrication of dual‐channel charge transmission mode are crucial to developing highly effective photocatalysts. However, constructing double charge transfer paths by loading dual cocatalysts in a nanocomposite is still a great challenge. Here, hollow Co9 S8 nanocages are utilized to design a hierarchical Co9 S8 /CdIn2 S4 /Pt heterostructure with dual‐channel for charge transfer, in which Co9 S8 nanocages and Pt particles act as cocatalysts. Moreover, Co9 S8 and CdIn2 S4 form an atomic interfacial contact by intermediate sulfur atoms. Due to double‐channel charge transfer and atomic interfacial bonding, the Co9 S8 /CdIn2 S4 /Pt nanocages accelerate the photo‐induced carriers transfer and suppress the combination of electron–hole pairs. As a result, the Co9 S8 /CdIn2 S4 /Pt nanocages exhibit increased photocurrent density of 62.8 µA cm −2, far exceeding that of pristine Co9 S8 (6.87 µA cm −2 ). The optimized Co9 S8 /CdIn2 S4 /Pt nanocages display excellent photocatalytic H2 in production rate of 13 426 µmol g −1 h −1 and high cyclic stability for water splitting. Abstract : A Co9 S8 /CdIn2 S4 /Pt heterostructure with an atomic interfacial contact and dual‐channel for charge transfer is designed and fabricated. The dual‐Z‐scheme system can extremely accelerate the photo‐induced carriers transfer and enhances the photocatalytic activity. The Co9 S8 /CdIn2 S4 /Pt heterostructure shows extraordinary photocatalytic activity of around 13 426 µmol g −1 h −1 under visible light illumination and outstanding cycling stability.